ANTIDIABETIC ACTIVITY OF METHANOLIC EXTRACT OF MEMECYLON MALABARICUM COGN (MELASTOMATACEAE) LEAVES - M. RAMAIAH,; B. GANGA RAO,; G. CHAKRAVARTHI, (International Journal of Pharma and Bio Sciences, 2013)
Memecylon malabaricum cogn (Melastomataceae) is an indigenous medicinal plant used in ethno medicine for the treatment of bacterial infections, inflammation and skin diseases including herpes, chickenpox. It’s also a root ecbolic. The methanolic extract of Memecylon malabaricum leaves is subjected to antidiabetic activity using experimental model of alloxan induced diabetes. The results showed that the methanolic extract at the dose of 400 mg/kg body weight showed significantly decreased (P<0.01) of the raised blood glucose level, comparable to reference standard, gliclazide. The preliminary phytochemical analysis reveals that the plant possessing steroids, saponins, flavonoids, tannins, and alkaloids. The antidiabetic activity of the plant may be due to the presence of the above said category of compounds. It is therefore worth study further to isolate the pure molecules responsible for antidiabetic activity. In conclusion, the results of this study explicate justification of the use of this plant in the treatment of diabetes.